Integrasi Nilai-nilai Pendidikan Islam dan Konsep Lifelong Learning dalam Kurikulum Madrasah - Asep Khaerul Faizin; Dhani Sudirman (EduInovasi: Journal of Basic Educational Studies, 2025)
The integration of Islamic educational values and the concept of lifelong learning is an urgent need to address the challenges of 21st-century education, particularly in madrasah environments, which play a strategic role in shaping students' character and competencies from an early age. This study aims to analyze the forms and mechanisms of integration of Islamic educational values with the concept of lifelong learning in the curriculum of the Tarbiyatul Athfal Elementary Madrasah. This study uses a qualitative approach with a case study. Data collection techniques were carried out through observation, in-depth interviews, and documentation studies of teachers, madrasah principals, and curriculum documents. Data analysis was conducted inductively through the processes of reduction, presentation, and drawing conclusions. The results show that this integration is realized through four main aspects: values-based learning strategies and reflection, the role of teachers as a liaison between Islamic teachings and long-term learning competencies, a school culture that supports contextual learning, and curriculum documents that include indicators of reflective and applicable learning. Educational practices in this madrasah illustrate a concrete effort to align Islamic teachings with the principles of lifelong learning. The implications of this study confirm that basic Islamic education has the potential to develop a holistic curriculum that is relevant to today's demands. This research contributes to the development of madrasa curriculum policies and practices that are oriented towards values and sustainability of learning.